Analysis of Academic Stress Factors and Their Impact on Academic Achievement of Mathematics Education Students - Yuyun Yunarti; Fertilia Ikashaum; Endah Wulantina; Juitaning Mustika; Dwi Retno Puspita Sari (Universitas Syiah Kuala, 2024)
Changes in the learning system and high academic demands put pressure on first- and second-year bachelor's mathematics education students and, therefore, can affect students' academic achievement. The purpose of this study was to examine academic stress factors and their impact on the educational achievement of mathematics education students in 80 respondents using a descriptive quantitative approach. This study discusses adolescent academic stress factors and covers students' physical and psychological well-being. The data obtained were analyzed using factor analysis. Exploratory factor analysis extracted 30 daily stress factors of students into three specific stress factors: stress on lecture material, environment, and time management. The results of this study indicate that students have moderate levels of stress. Then, Pearson analysis was conducted to see the correlation between stress factors and cumulative grade point average. The results showed that the three factors did not significantly correlate to grades with a correlation power below 0.5. This means that students can manage their academic stress well.Student stress management approaches can focus on each factor separately, depending on individual needs. Internal and external support, strengthening academic literacy, improving conducive learning environment facilities, relevant skills development programs, and strengthening social networks can help reduce student stress.